Vocational education and training and the Great Recession: supporting young people in a time of crisis - Heyes, Jason (Brussels, 2014)
" During the last five years training and education policies have received strong support at European and international levels. Emphasis has been placed on Initial Vocational Education and Training (IVET) and apprenticeships – which enable workers to gain a foothold in the labour market – and on Continuous Vocational Education and Training (CVET) which is important for maintaining their employability. The report provides a detailed overview of several European countries and their VET policies before and after the onset of the crisis. It sets outs to answer the following questions: How have EU member states responded to the dire economic and social situation and to the international call to improve IVET opportunities for young people? Has the crisis provoked a convergence of strategies across member states? Have the changed circumstances altered the governance of VET institutions, or the actors involved?